Assessment of Retroviruses as Potential Vectors for the Cell Delivery of Prions - Rahimi Khameneh, Shabnam (Université d'Ottawa / University of Ottawa, 2012)
Transmissible spongiform encephalopathies (TSEs) or prion diseases are a class of fatal brain disorders better known as Creutzfeldt-Jacob Disease (CJD) in humans, bovine spongiform encephalopathy (BSE) in cattle, scrapie in sheep, and chronic wasting disease (CWD) in deer and elk. The infectious agent responsible for these diseases is a misfolded prion protein capable of catalyzing a conformational change in normal cellular prion proteins (PrPC) into aberrant disease-causing structural isoforms (PrPSc). Although the etiological agent for TSEs has clearly been defined as PrPSc, there are important gaps in our understanding of how these proteins target and invade brain tissue. It remains to be established how ingested PrPSc ultimately reach the brain and also to understand why these tissues are particularly targeted, notwithstanding that several other tissues highly express prion proteins. Certain viruses, retroviruses in particular, efficiently hijack host proteins and can carry these proteins with them when they are released from a cell. Several lines of evidence have shown that prions and retroviruses can interact and associate at various stages of the retroviral replication cycle. Of special interest is that most retroviruses can cross the blood-brain barrier and could therefore deliver host-derived proteins to neuronal cells. In view of these observations, this thesis investigates whether retroviruses can act as vectors to capture prions from an infected cell and deliver them to a susceptible target cell. In this work, I have cloned human and mouse prion cDNAs from PBMCs and the murine cell line NIH 3T3. Either a FLAG epitope tag or the eGFP reporter protein cDNA was inserted into a region of the prion cDNA that is predicted to be amenable to such genetic insertions without affecting protein folding or expression. I then confirmed using both fluorescent and confocal microscopy and that the recombinant proteins had a similar cell distribution to the endogenous prion protein. Using Western blot analysis, I then showed that endogenous and overexpressed prion proteins can be detected in co-transfected cells producing HIV and murine leukemia virus (MLV) retroviral particles. Finally, I went on to show that prions are also present at high levels in HIV and MLV retroviral particles released from these cells. This work constitutes the first step in determining whether retroviruses can act as vectors for prion dissemination. Establishing a strong and clear association between retroviruses, pathogenic prions and prion disease would provide the rationale for preventive measures to be taken directly against retroviruses in order to protect humans and animals that have been newly exposed to PrPSc-infected products or those who are genetically predisposed to develop prion diseases. Anti-retroviral drugs could also be potentially used to delay disease progression and reduce prion transmission in human and animal tissues. The availability of such a treatment would constitute a significant advancement because there is currently no cure or treatment for prion diseases.
Keywords: Prion; Prion diseases; Retroviruses; MLV; HIV; Vector; FLAG epitope tag; eGFP reporter protein; Prion protein constructs; NIH3T3 cell; HEK 293T cell; Confocal fluorescent microscopy